Copy number variants of Ras/MAPK pathway genes in patients with isolated cryptorchidism. (10th July 2017) - Rodríguez, F.; Vallejos, C.; Giraudo, F.; Unanue, N.; Hernández, M. I.; Godoy, P.; Célis, S.; Martín‐Arenas, R.; Palomares‐Bralo, M.; Heath, K. E.; López, M. T.; Cassorla, F.
Summary: Cryptorchidism is the most common congenital disorder in boys, but the cause for most cases remains unknown. Patients with Noonan Syndrome are characterized by a typical face, growth retardation, congenital heart defects, learning disabilities and cryptorchidism. Copy number variations of Ras/MAPK pathway genes are unusual in patients with several clinical features of Noonan Syndrome; however, they have not been studied in patients with only one feature of this condition, such as cryptorchidism. Our aim was to determine whether patients with isolated cryptorchidism exhibit Ras/MAPK pathway gene copy number variations (CNVs). Fifty‐nine patients with isolated cryptorchidism and negative for mutations in genes associated with Noonan Syndrome were recruited. Determination of Ras/MAPK pathway gene CNVs was performed by Comparative Genome Hybridization array. A CNV was identified in two individuals, a ~175 kb microduplication at 3p25.2, partially including RAF1 . A similar RAF1 microduplication has been observed in a patient with testicular aplasia. This suggests that some patients with isolated cryptorchidism may harbor Ras/MAPK pathway gene CNVs.